Formulation of physio-mechanical properties towards enhancing hybrid banana kenaf reinforced bio-composites - Dhar Malingam, Sivakumar; Subramonian, Sivarao; Selamat, Mohd Zulkefli; Sheikh Md Fadzullah, Siti Hajar; Ab Ghani, Ahmad Fuad; Zulkafli, Norizzati (UTeM, 2019)
To date, the increasing awareness towards a green future has brought many recyclable and biodegradable things into our daily lifestyle. The ever-increasing demand for green composite will continue to grow with the desire for more durable and lighter materials. However, natural fibres as reinforcement are insufficient to satisfy the technical needs of a composite. Therefore, embedding commonly available E-glass fibre into banana fibre reinforced composite will enhance the overall properties. For these reasons, natural fibres considered as one of the alternatives in reducing the impact on the environment in terms of renewability, recyclability, biodegradability, sustainability, health and eco-friendly. Banana fibre is used in this research, however, limited research on the hybrid cross-ply banana/glass fibre reinforced polypropylene composite is available. Thus, this research aims to determine the effect of fibre lay-up sequence on the mechanical, physical properties and effect of moisture absorption on the mechanical properties. The mechanical properties comprise of tensile, flexural, quasi-static indentation and low-velocity impact and comparison between dry and wetted specimens of tensile and flexural tests. Both cross-ply banana (B) and glass (G) fibre were cut into dimensions of 250 x 250 mm and stacked alternately with polypropylene sheets. The four different lay-up sequences of composites (BBB, BGB, GBG and GGG) were hot-pressed and cut into test dimensions according to ASTM standards with thickness determined by ply stacking lay-up. Tensile and flexural tests were done according to ASTM D3039 and ASTM D790 respectively with a speed rate of 2 mm/min. Quasi-static indentation (QSI) and low-velocity impact (LVI) tests were done according to ASTM D6264 and ASTM D7136 respectively. The speed rate for QSI is 1.27 mm/min and impact velocity speed for LVI is 4.5 m/s. The water absorption test is conducted according to ASTM D570. Embedding glass fibre to banana fibre reinforced composite shows promising improvement by 253.52% and 780.49% for GBG in terms of tensile strength and modulus. The incorporation of glass fibre as the skin layer improves the GBG flexural strength and modulus by 17.50% and 86.83% compared to BBB. The energy absorption for GBG also was improved by 161.27% and 188.57% for quasi-static indentation and low-velocity impact respectively. Besides, the incorporation of glass fibre reduced the moisture absorption rate by 66.99% for GBG while thickness swelling decreased by 29.01%. As for the effect of moisture on the tensile and flexural properties, the tensile strength and modulus of GBG were reduced by 1.34% and 16.34% when compared to dry samples. Contradict with the tensile properties, the flexural strength and modulus of wetted GBG increased by 13.07% and 12.50% respectively. In terms of stacking sequence, the wetted tensile strength and modulus of GBG increased from BBB by 439.74% and 978.57%. Flexural strength and modulus also increased from BBB to GBG by 46.43% and 126.45% respectively. The results showed that hybrid banana/glass fibre reinforced polypropylene composite could be commercialised for mid-range load applications.